MANAJEMEN PERUBAHAN PELAYANAN PENDIDIKAN PADA ERA PANDEMIC COVID 19 DI UNIVERSITAS BATURAJA - Hesti Lingga Putri Putri; Herni Ramayanti (JURNAL DINAMIKA, 2021)
Education is an effort to educate the nation's life and improve the quality of human resources conducted by giving knowledge or so-called learning in the life of a human being that starts early. University is a college, where people continue after completing high school education to obtain higher education and personality as well as a bachelor's degree. Universities should be able to provide quality services and have competitiveness and affordable for the community. Problems that arise such as changes in the teaching and learning process, obstacles in the fulfillment of internet kuaota. Then it can be carried out the goal to carry out the teaching and learning process or there is a change in the management of services in education and to find a clear solution of obstacles in the fulfillment of internet quotas that must be met descriptive method with qualitative approach. Learning in college is organized in a mix – face-to-face and in-network (hybrid learning). Nevertheless, universities must still prioritize the health and safety of campus residents (students, lecturers, tendik) and the surrounding community. The results of this study are welcomed by the education world by implementing home learning using classroom applications, zoom applications, Edmodo applications and learning through the internet is carried out during the covid-19 pandemic and the validity period is not determined. Overcome the constraints of data charging or pulse can also be controlled with the help of parties related to the world of education and welfare for the community.